Identification of circulating tumor cells using 4‐color fluorescence in situ hybridization: Validation of a noninvasive aid for ruling out lung cancer in patients with low‐dose computed tomography–detected lung nodules. Issue 8 (22nd April 2020) - Katz, Ruth L.; Zaidi, Tanweer M.; Pujara, Deep; Shanbhag, Namita D.; Truong, Duy; Patil, Shekhar; Mehran, Reza J.; El‐Zein, Randa A.; Shete, Sanjay S.; Kuban, Joshua D.
Abstract : Background: Approximately one third of needle biopsies that are performed to rule out malignancy of indeterminate pulmonary nodules detected radiologically during lung cancer screening are negative, thus exposing cancer‐free patients to risks of pneumothorax, bleeding, and infection. A noninvasive confirmatory tool (eg, liquid biopsy) is urgently needed in the lung cancer diagnosis setting to stratify patients who should receive biopsy versus those who should be monitored. Methods: A novel antigen‐independent, 4‐color fluorescence in situ hybridization (FISH)‐based method was developed to detect circulating tumor cells (CTCs) with abnormalities in gene copy numbers in mononuclear cell–enriched peripheral blood samples from patients with (n = 107) and without (n = 100) lung cancer. Results: Identification of CTCs using FISH probes at 10q22.3/CEP10 and 3p22.1/3q29 detected lung cancer cases with 94.2% accuracy, 89% sensitivity, and 100% specificity compared with biopsy. Conclusion: The high accuracy of this liquid biopsy method suggests that it may be used as a noninvasive decision tool to reduce the frequency of unnecessary needle biopsy in patients with benign pulmonary lesions. Abstract : A noninvasive confirmatory tool (eg, liquid biopsy) is urgently needed in the lung cancer diagnosis setting to stratify patients who should receive biopsy versus those who should be monitored. This study describes the high accuracy and specificity of a new liquid biopsy technology based on 4‐color fluorescence in situ hybridization, supporting its use as a noninvasive decision tool to rule out malignancy of indeterminate pulmonary nodules.